HOW DOES THE MEANING THAT CONSUMERS DERIVE FROM ADVERTISEMENTS VARY ACROSS CULTURE? - Mohanasundaram, Arun Pragash (2010)
Due to the convergence of homogenous consumer needs, taste and lifestyle, the globalization of media, incomes and technology were expected. But many researchers debated that adaptation is needed in the place of standardization in many places especially in the field of advertising. The aim of this dissertation is to analyze the influence of culture in advertising and also to show how does the meaning that consumers derive from advertisements, vary across cultures. The influence of culture in a person‟s perception of the meaning in the advertisement will be analyzed in this research. This is achieved by analyzing how the meaning derived by the Chinese and Indian people from the same advertisement varied based on their cultural influence. By studying the concepts of culture and using those concepts to compare the way Chinese and Indian participant interpreted the same advertisements, this research will highlight the importance of advertising based on culture when advertising across nations. Using primary research the difference in the advertisements of the different nations in terms of culture is studied. The research finding will show how the consumers from different cultures interpreted the same advertisement differently. Finally the different factors to be considered while advertising across cultures will also be discussed.